1994
DOI: 10.1099/00222615-40-2-95
|View full text |Cite
|
Sign up to set email alerts
|

Adherence of non-enteropathogenic Escherichia coli to HeLa cells

Abstract: Summary. Three hundred and nine strains of Escherichia coli isolated from infants and children with diarrhoea but not belonging to any recognised classes of diarrhoeagenic E. coli were investigated for their ability to adhere to HeLa cells in the presence of D-mannose. An enteroadherent-aggregative pattern (EAgg) was observed in 32-03 YO, localised adherence (LA) in 4.5 YO, diffuse adherence (DA) in 5.8 YO, and LA/DA and EAgg/LA in 1.9 YO and 1.2 YO of the isolates respectively. The results obtained with 100 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0
3

Year Published

1998
1998
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 0 publications
1
22
0
3
Order By: Relevance
“…The association of certain serogroups of EPEC with endemic infantile diarrhoea has also been reported from several countries, including Bangladesh (6), Saudi Arabia (11), Brazil (25), Uruguay (2), and in several studies (3, 23). Results of a study in Iran showed that 65% of isolates identified by commercial antisera were probably a putative EPEC (26), and although O serogrouping is not a perfect tool, in our setting it is still a useful method for presumptive identification of these strains.…”
Section: Discussionmentioning
confidence: 73%
“…The association of certain serogroups of EPEC with endemic infantile diarrhoea has also been reported from several countries, including Bangladesh (6), Saudi Arabia (11), Brazil (25), Uruguay (2), and in several studies (3, 23). Results of a study in Iran showed that 65% of isolates identified by commercial antisera were probably a putative EPEC (26), and although O serogrouping is not a perfect tool, in our setting it is still a useful method for presumptive identification of these strains.…”
Section: Discussionmentioning
confidence: 73%
“…Although LA/AA co-expression in some human E. coli has been previously reported by Bouzari et al (6), further information on these isolates is lacking. Moreover, since the expression of LA and AA is used to classify fecal E. coli as typical EPEC and EAEC (1,3), respectively, the classification of such strains within the DEC pathotypes is difficult.…”
Section: Escherichia Colimentioning
confidence: 92%
“…TOSV has also been isolated from the brain of a bat in areas where P. perniciosus and P. perfiliewi were present, but no hemagglutinationinhibiting antibodies were found in sera from these bats (5). In Spain, 2 isolates of TOSV were recovered from 103 pools of sandflies; sequence analyses showed that they were genetically divergent from the Italian strains (6). To date, TOSV had not been isolated from sandflies collected in France.…”
Section: Escherichia Colimentioning
confidence: 99%
“…10 DNA was extracted by means of the alkaline lysis method and dotted to nitrocellulose. 11 Hybridization was performed under stringent conditions by the digoxigenin labeling and detection system (Boehringer Mannheim, Indianapolis, IN).…”
mentioning
confidence: 99%